2011
DOI: 10.2741/s127
|View full text |Cite
|
Sign up to set email alerts
|

Management of type-2 diabetes with anti-platelet therapies special reference to aspirin

Abstract: Adult onset diabetes currently affects 380 million individuals worldwide and is expected to affect 380 million by 2025. Major defects contributing to this complex disease are insulin resistance and beta cell dysfunction. More than 80% of patients professing to type-2 diabetes are insulin resistant. Recent studies have shown that the Indian subcontinent ranks very high in the occurrence of Diabetes and Coronary artery disease (1, 2, 3). Patients with Type 2 diabetes carry an equivalent cardiovascular risk to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…also reported that antiplatelet treatment can reduce vascular dysfunction. [10] Magen et al . in a study at 2005 showed that addition of low-dose aspirin to antihypertensive treatment and statins in hypertensive and hypercholesterolemic patient can reduce systolic and diastolic blood pressure through improved NO-mediated endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…also reported that antiplatelet treatment can reduce vascular dysfunction. [10] Magen et al . in a study at 2005 showed that addition of low-dose aspirin to antihypertensive treatment and statins in hypertensive and hypercholesterolemic patient can reduce systolic and diastolic blood pressure through improved NO-mediated endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease is the primary cause of death in diabetic patients aged > 65 years (about 70%), whereas cerebrovascular disease is the primary cause of death in about 15% [ 1 , 2 ]. The most frequent causes of thrombotic events in T2DM are the following: impaired platelet function (increased processes of adhesion, aggregation, and activation, increased platelet turnover), endothelial dysfunction (increased expression of adhesion molecules, enhanced production of vasoconstrictors such as angiotensin II, endothelin 1, thromboxane etc., decreased production of vasodilators such as nitric oxide, increased oxidative stress) and impaired fibrinolysis [ 3 5 ]. Until 2010, the use of acetylsalicylic acid (ASA) for cardiovascular protection had been recommended to each diabetic patient.…”
Section: Introductionmentioning
confidence: 99%
“…Eighty percent of Type-2 diabetes is preventable by changing diet, increasing physical activity and improving the lifestyle. As a part of its Global mission to promote diabetes care and prevention, International Diabetes Federation develops guidelines, which review evidence to date on post-meal-glucose values and the development of clinical complications of diabetes [10]. These guidelines and recommendations are intended to help clinicians and professional organizations in developing strategies for effective management of PMG in diabetics.…”
mentioning
confidence: 99%
“…All Gulf countries have very high incidence of type-2 diabetes. According to the international Federation Guidelines, there is increasing evidence that supports the importance of controlling or managing all the three components of the glucose triad; hemoglobin A1c, Fasting Glucose, and Post Prandial Glucose [10]. Post-meal glycemia (PMG) is defined as 140 mg of glucose/dl, 2 hr after the ingestion of a meal.…”
mentioning
confidence: 99%
See 1 more Smart Citation